Land Ethics and Ecological Narratives in Patricia Wrightson's the Nargun and the Stars and the Rocks of Honey - Dr. Nancy Pearlin (International Journal of Scientific Research in Science and Technology, 2024)
This paper aims to address the intrinsic relationship between literature, land ecology and the people. The ecological perspective of comprehending the land gives insight into the evolution of ethics that are imperative for the conservation of the natural environment. The study highlights the aspect of Land Ethics in Patricia Wrightson’s Nargun and the Stars and The Rocks of Honey. It delineates on the aspect of land ethics and the essentiality of how all life forms are one large interlocked network. It also touches upon the Australian Aboriginal myth and the need to protect and preserve the land.
Keywords: Land Ethics; Australian Aboriginal; Children’s Literature; Patricia Wrightson; Ecology